Isotherm and kinetic adsorption study of dye by spent tea leaf - Teh Jian Haur (School of Environmental Engineering, University Malaysia Perlis, 2012)
Dye effluent is a significant contaminant to the environment and health and essential to be treated properly. There are numerous of treatment methods had been applied at present day but were end up with limitation itself. Adsorption is one of the common treatment methods which have a great advantage in term of simple operation and leave no harm to the environment. Searching for low cost adsorbent being focus recently because activated carbon be the only obstacle. Spent tea leaf had been proposed to remove synthetic basic dye from aqueous solution in this final year project. The operating parameter of batch and column has been conduct and the analysis was done in term of isotherm and kinetic. The results show a 99 % removal had achieve in the contact time within 15 to 60 minutes, 0.3 g of adsorbent dosage in 100 mg/L dye solution. Besides that, it also shows 84.75 mg/g of maximum adsorption capacity and 0.3508 g/mg.min of pseudo second order kinetic rate constant. The result show that spent tea leaf is capable being considered as alternative adsorbent.